Dinamika Sosiolinguistik Masyarakat Dwibahasawan: Analisis Penggunaan Alih Kode dan Campur Kode dalam Interaksi Digital - Nur Syakila; Tessalonika Simangunsong; Lolo Mesliana Cibro; Ayu Nadira Wulandari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to describe and analyze the sociolinguistic phenomena of code-switching, code-mixing, interference, and integration in digital interactions among bilingual communities. The method used is descriptive qualitative, using listening and note-taking techniques for WhatsApp speech. The results show that code-switching occurs in whole sentences (Indonesian-English and Indonesian-Javanese), code-mixing occurs through the insertion of foreign terms such as